Patient Profiles of Potts Diseases: Experience of 50 Cases in a Tertiary Care Hospital in Dhaka City (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Spinal tuberculosis is a great problem in the health sector. Objective: The purpose of the present study was to see the see the socio-demographic characteristics of spinal tuberculosis patients. Methodology: This study was designed as descriptive cross sectional study which was carried out in the Department of Neurosurgery at Dhaka Medical College Hospital during the period of January 2002 to December 2004 for a period of two (2) years. All the patients who were presented with spinal tuberculosis at any age with both sexes were included as study population. The details of socio-economic condition were recorded of all the patients. Confirmation of spinal tuberculosis was made by CT-scan and MRI. Finally biopsy was done to confirm the cases by histopathology.Results: In this study, 50 cases of tuberculosis of the spine patients were recruited for this study. The mean age with SD was 25.4±18.65 years. The sex distribution shows male preponderance with a male and female ratio of 1.63:1. Regarding the socioeconomic status 33 (66%) patients came from low class society. In this study majority of the study population were illiterate which was 19(38.0%) cases. Most of the patients were day labourer which was 17(34.0%) cases.Conclusion: In conclusion young adult male patients are most commonly affected by spinal tuberculosis.Journal of National Institute of Neurosciences Bangladesh, 2016;2(2): 48-50